KONSEKUENSI, HUKUM, DAN DAMPAK SOSIAL PERNIKAHAN SIRI TERHADAP PEREMPUAN DAN ANAK MENURUT KOMPILASI HUKUM ISLAM DAN UNDANG-UNDANG PERNIKAHAN. - Citra Qur'ani Gunawan (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
Marriage is a sacred bond between a man and a woman whose aim is to form a sakinah, mawaddah and warahmah family. However, in reality, quite a few marriages experience problems, one of which is unregistered marriages or what can also be called unregistered marriages. Siri marriage is a marriage that is carried out with several provisions that have been outlined and determined by religion or must fulfill customary requirements by fulfilling predetermined requirements, but it is not recorded at the Religious Affairs Office (KUA). This research aims to analyze unregistered marriages and determine the consequences, legal and social impacts on women and children. The method used is normative research with literature study. The research results show that marriage in Islam has conditions, harmony, goals and legal consequences that must be fulfilled by the parties. Siri marriages are carried out without a legal guardian, and this research also discusses the views of ulama regarding the law of sirri marriages, state laws regarding these marriages, as well as the negative impacts that can arise as a result of sirri marriages. An unregistered marriage entered into by someone can cause many problems in the future, especially related to administration, maintenance rights for children and wife, as well as inheritance rights and guardian rights fo children born from the marriage. Keywords: Siri Marriage, Islamic Law, Laws, and Marriage Registration